1989
DOI: 10.1128/aac.33.9.1526
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoxia and the antimicrobial susceptibility of Escherichia coli and Pseudomonas aeruginosa

Abstract: We have tested the ability of hyperoxia (98% 02-2% CO2 at 2.8 atmospheres absolute [ca. 284.6 kPa]) to enhance killing of Escherichia coli (serotype 018 or ATCC 25922) by nitrofurantoin, sulfamethoxazole, trimethoprim, gentamicin, and tobramycin. We have also looked for interactions between hyperoxia and the aminoglycosides against Pseudomonas aeruginosa ATCC 27853. Hyperoxia significantly enhanced bacteriostatic activity of nitrofurantoin and trimethoprim as measured by MIC testing. The possibility exists th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“…After the 1-h exposure, tobramycin was removed and the bacteria were incubated under normoxic conditions. The maximal killing of P. aeruginosa which occurred under normoxic conditions is in agreement with our previous work (25) (31), who found that hyperoxia enhances the growth of E. coli. Aminoglycoside uptake by bacteria has been shown to be dependent upon growth rates or quinonedependent bacterial respiration (26,27,29).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…After the 1-h exposure, tobramycin was removed and the bacteria were incubated under normoxic conditions. The maximal killing of P. aeruginosa which occurred under normoxic conditions is in agreement with our previous work (25) (31), who found that hyperoxia enhances the growth of E. coli. Aminoglycoside uptake by bacteria has been shown to be dependent upon growth rates or quinonedependent bacterial respiration (26,27,29).…”
Section: Discussionsupporting
confidence: 81%
“…Exposure to hyperbaric oxygen for 18 to 24 h inhibited the growth of P. aeruginosa (4,19,25 (12). Hyperoxia may extend the in vivo PAE and therefore prolong the therapeutic activity of aminoglycosides in patients exposed to hyperoxia or hyperbaric oxygen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Air may have a bacteriostatic effect. Air components such as oxygen and carbon dioxide have bacteriostatic properties, and potentiate antibacterial effects of some antibiotics [17][18][19][20]. In addition, oxygen and nitrogen are used in the production of reactive oxygen and reactive nitrogen intermediates.…”
Section: Discussionmentioning
confidence: 99%
“…12 Despite controversy over the treatment of spinal tuberculosis, we added hyperbaric oxygen (HBO) therapy to our treatment protocol to take advantage of its proven antibactericidal effects. [15][16][17][18][19][20] Data obtained from control and study groups were compared to evaluate the effect of adjuvant HBO therapy on the duration of chemotherapy and rate of radiological improvement in spinal tuberculosis.…”
Section: Introductionmentioning
confidence: 99%